ENKRIPSI SMS DENGAN MENGGUNAKAN MODE CIPHER FEEDBACK (CFB) 8-BIT BERBASIS ANDROID - Siska Ayu Widiana; Iqbal Firdaus (Politeknik Negeri Indramayu, 2023)
The purpose of this research is to reduce the factors of SMS security by using SMS encryption application using cipher feedback 8-bits mode on android device. The first factor, which is the physical factor, is if the mobile phone is held by another person who are not the owner of the phone. That person can read and get information from the message on that mobile phone. The second factor is the safety messages in the system, this is all because the provider of mobile phones is only encrypting the messages during the transmission process, while in the storage process in the provider of mobile phones, the messages is saved as plaintext. The step of the process on cipher feedback 8-bits mode is started from filling the SMS with plaintext and initialization vector (IV) and key. Then the encryption function will process them to produce the keystream. The early 8 bits of keystream will be exclusive-or-ed (XORed) by the early 8 bits of plaintext and the result will be sent back to left most block from early IV with shift register process, and these processes will be repeated until resulting a chipertext message filled by rows of hexadecimal. The ciphertext as a result from the system will be sent to the receiver through the server, so the real message which is addressed to the receiver will be safe. Based on the result above, it can be concluded that the message would not be read except by the sender and the receiver.